2016
DOI: 10.1080/13880209.2016.1265987
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and antioxidant activity of Lycium barbarum (Goji) cultivated in Greece

Abstract: Context: The fruit of Lycium barbarum L. (Solanaceae), known as goji berry, has been exploited for a long time in traditional Chinese medicine. In recent decades, it has received much attention as one of the trendiest functional foods with a wide array of pharmacological activities in Western diets.Objective: In this study the phenolic profile and potential antioxidant capacity of Lycium barbarum cultivated in Crete (Greece) were investigated.Materials and methods: The berries were defatted with hexane and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 24 publications
(25 reference statements)
4
33
3
3
Order By: Relevance
“…The results of the present study show that the methanol extract has a higher phenol and flavonoid content than the water extract, and so has a higher radical scavenging activity. These results concur with the previous observation identifying the strong free radical scavenging activity of L. barbarum extracts [21,22]. However, due to differences in the experimental procedures between the studies in the use of a DPPH assay, inconsistent results were observed.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results of the present study show that the methanol extract has a higher phenol and flavonoid content than the water extract, and so has a higher radical scavenging activity. These results concur with the previous observation identifying the strong free radical scavenging activity of L. barbarum extracts [21,22]. However, due to differences in the experimental procedures between the studies in the use of a DPPH assay, inconsistent results were observed.…”
Section: Discussionsupporting
confidence: 88%
“…The phenolic content values obtained in this study were lower than in the studies reported by Benchennouf et al and Vulić et al [21,22]. These inconsistencies may stem from differences in extraction procedure, although in general, polyphenol extraction from plant material is influenced mainly by solvent polarity [23].…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Fortification of vitamin D in food matrix also brings limitation within it, which is degradation of vitamin D in target food (Tangpricha et al, 2003;Wagner et al, 2008). one of the well reported berry rich in diverse groups of phytochemicals (Benchennouf et al, 2017;Chen et al, 2014;Vulić et al, 2016;Yang et al, 2015;Zhang, 2013;Zhang et al, 2016). Recent literature suggests that addition of natural fruits extract, rich in phenolic contents, offers high antioxidative properties as well as various other health benefits (Cossu et al, 2009;El-Said et al, 2014;Karaaslan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%